A national nudge study of differently framed messages to increase COVID-19 vaccine uptake in Saudi Arabia: A randomized controlled trial - Mohammed Alhajji; Abdullah H. Alzeer; Rami Al-Jafar; Reem Alshehri; Saad Alyahya; Sara Alsuhaibani; Sarah Alkhudair; Raghad Aldhahiri; Ahmed Alhomaid; Dalal Alali; Abdulelah Alothman; Eman Alkhulaifi; et al. (Elsevier, 2023)
Background: During the COVID-19 pandemic, Saudi Arabia witnessed hesitancy from a proportion of the population toward taking the vaccine; thus, it was necessary to nudge them to uptake it. This study was conducted to assess the impact of using different types of messages to nudge the public to increase the proportion of vaccinated individuals. Methods: This study is a multi-arm randomized controlled trial aiming to assess the efficacy of using differently framed messages that appear as pop-notifications in Sehatty application. Of those who preregistered to receive a COVID-19 vaccine but didn't take it according to the Saudi national vaccine registry (n = 1,291,686), 12,000 individuals were randomly recruited and randomly assigned to one of five intervention groups (commitment, loss aversion, salience, social norms, and ego) or a control group. To ensure the exposure occurred in the intervention groups, we included only those who received the notification, which was confirmed by checking the information technology system. We used the Chi-square test to compare each intervention group against the control group separately. Also, we used the same test to investigate whether sex and age influenced the percentage of booked appointments in the intervention groups. Results: Social norms, ego, salience and loss aversion groups had higher percentages of booked appointments when compared to the control group (21.0%, p = 0.001; 19.1%, p = 0.011; 19.0%, p = 0.013; 18.4%, p = 0.034, respectively). Moreover, when combining the intervention groups, the percentage was higher than the control group (p < 0.001). The percentages of booked appointments made by Young adults (18-35 years old) were higher than that of adults over 35 years old in the social norms (22.6%, p = 0.016) and ego groups (21.0%, p = 0.010). At the same time, sex didn't affect the percentages of booked appointments in any group. Conclusion: Using different framings of messages to nudge the public to take vaccines can help increase the percentage of immunized individuals in a community. Nudges can boost the public health of a population during an unusual spread of vaccine-preventable diseases. Findings might also inspire governmental responses to other public health situations.